2015
DOI: 10.3171/2015.9.focus15355
|View full text |Cite
|
Sign up to set email alerts
|

The National Neurosurgery Quality and Outcomes Database Qualified Clinical Data Registry: 2015 measure specifications and rationale

Abstract: Meaningful quality measurement and public reporting have the potential to facilitate targeted outcome improvement, practice-based learning, shared decision making, and effective resource utilization. Recent developments in national quality reporting programs, such as the Centers for Medicare & Medicaid Services Qualified Clinical Data Registry (QCDR) reporting option, have enhanced the ability of specialty groups to develop relevant quality measures of the care they deliver. QCDRs will complete the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 150 publications
0
18
0
1
Order By: Relevance
“…In an attempt to curb increasing expenditures, the Centers for Medicare and Medicaid Service, private insurers, and other health care purchasers have initiated several cost containment and quality improvement measures. 5,9,37 Perhaps the most common among these novel payment and quality improvement programs is capitated bundled care contracting for spine surgery and other health care services. These contracts require hospitals and their physicians to "bundle" facility and professional charges for necessary care throughout a defined longitudinal episode of care, and to assume all risk of cost/utilization overruns.…”
mentioning
confidence: 99%
“…In an attempt to curb increasing expenditures, the Centers for Medicare and Medicaid Service, private insurers, and other health care purchasers have initiated several cost containment and quality improvement measures. 5,9,37 Perhaps the most common among these novel payment and quality improvement programs is capitated bundled care contracting for spine surgery and other health care services. These contracts require hospitals and their physicians to "bundle" facility and professional charges for necessary care throughout a defined longitudinal episode of care, and to assume all risk of cost/utilization overruns.…”
mentioning
confidence: 99%
“…Although eCQMs require a significant upfront investment in development, testing, and deployment, they have potential to decrease measurement burden over time for practicing clinicians (5). Moreover, generating reports at both local and national levels through the use of aggregated patient registries has started to facilitate rapid cycle quality improvement efforts in some specialties (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Various approaches in studying cost-effectiveness in lumbar spine surgery have previously been performed for specific patient populations, such as patients with spondylolisthesis and those with scoliosis and when surgical approaches like MIS are used. 2,4,5,7,9,12,15,[19][20][21] For example, Parker et al 18 evaluated variables affecting cost of fusion and nonfusion spine surgeries using the National Neurosurgery Quality and Outcomes Database (N 2 QOD). This study identified length of stay, number of admission diagnoses and procedures, hospital size and region, patient income, fusion surgery, acute renal failure, sex, and coagulopathy as common drivers of cost.…”
Section: Cost-effectiveness Research In Spine Surgerymentioning
confidence: 99%